Determinants of muscle mass in hemodialysis patients: the role of BMI, MUAC, and MAMC - Widiany, Fery Lusviana; Metty, Metty; Inayah, Inayah; Nurtyas, Maratusholikhah; Byo, Wa Ode Windra; Anggunita, Fiolla; Pratama, Adams Bagus (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
ABSTRACTBackground: Previous experimental research on oral nutritional support formulas made from snails, tempeh, and moringa leaves, which are high in protein and calcium, has been reported to increase muscle mass in hemodialysis patients. However, further research is needed to analyze the factors that influence muscle mass in hemodialysis patients.Objective: To analyze factors that influence muscle mass in hemodialysis patients.Materials and Methods: This study was an observational study with a cross-sectional design. The study was conducted at Panembahan Senopati Bantul Hospital. The research sample was taken using a purposive sampling technique. The inclusion criteria for the study included being 18 years of age or older, undergoing routine hemodialysis 2 times a week, having received nutritional counseling, patients being able to stand, and being able to be measured anthropometrically. The exclusion criteria of the study were patients with anasarca edema, and patients whose muscle mass and bone mass could not be measured using bioelectrical impedance analysis (BIA). Independent variables suspected of influencing muscle mass included body mass index, mid-upper arm circumference (MUAC), triceps skinfold, mid-arm muscle circumference (MAMC), duration of hemodialysis, duration of hemodialysis, energy intake, protein intake, fat intake, carbohydrate intake, vitamin C intake, iron intake, and zinc intake. Research instruments include BIA/Bioelectrical Impedance Analysis to measure muscle mass, digital body scales with a scale of 0.1 kg, microtoise, metline, informed consent questionnaire, SQ-FFQ (Semi-Quantitative Food Frequency Questionnaire), CRF (Case Report Form), and research activity recording form. Data were analyzed univariately, bivariately, and multivariately.Results: The analysis showed that the relationship between BMI, MUAC, and MAMC with muscle mass showed P values=0.025; p values <0.05.Conclusion: BMI, MUAC, and MAMC factors have a significant relationship with muscle mass. The higher the BMI, MUAC, and MAMC, the higher the muscle mass.Keywords: Body mass index; hemodialysis patients; mid-upper arm circumference (MUAC); mid-arm muscle circumference (MAMC); muscle mass